Acceptability and implementation potential of a health literacy intervention to increase colorectal cancer screening in deprived areas: A qualitative study of patients and general practitioners participating in a cluster randomized controlled trial - Alix Boirot; Maria Claudia Addamiano; Clémence Casanova; Niamh M. Redmond; Géraldine Cazorla; Michel Rotily; Anne-Marie Schott-Petelaz; Christian Balamou; Zineb Doukhi; Myriam Kaou; Françoise Couranjou; Julien Mancini; et al. (PLoS ONE, 2025)
Background Colorectal cancer (CCR) is one of the leading causes of death worldwide. Early detection remains a highly effective strategy for curing this disease. In France, despite a free organised screening programme for people aged between 50 and 74, participation rates remain suboptimal. Socioeconomic position and health literacy levels exacerbate the situation, with the lowest screening rates observed in the most socially disadvantaged areas. This study assessed patients’ and General Practitioners’ (GP) views on the acceptability of an intervention to increase screening uptake using a simple brochure and video on the importance and process of CCR screening. Method We conducted a cross-sectional qualitative study using semi-structured interviews with patients (n = 24) and GPs (n = 22) who used or participated in the DECODE project intervention. The interviews were conducted by telephone or videoconference and analysed thematically using Nvivo software and dual independent coding. Results 95% of GPs expressed a clear preference for the video over the brochure. Patients had varied results with 50% preferring the video, as it demonstrated how to do the test, versus the brochure. The humorous and de-dramatising aspects of the video were the two key factors highlighted by interviewees. However, support from healthcare staff (GPs, nurses, etc.) is still essential, in supporting patients in prevention. This presents a challenge for GPs, who are frequently constrained by time limitations during consultations. Conclusion Our findings emphasize the need to tailor promotional materials for both patients and healthcare professionals to improve CCR screening uptake, balancing digital efficiency with maintaining core human relationships in healthcare. Such intervention can be integrated into different workflows. The addition of video into national CRC screening programs might also help. Targeting CRC screening interventions at provider-patient interactions, ensuring they are tailored, accessible, and engaging, is key to reducing disparities.